Promoting resilience in healthcare workers during the COVID-19 pandemic with a brief online intervention. (February 2022) - DeTore, N.R.; Sylvia, L.; Park, E.R.; Burke, A.; Levison, J.H.; Shannon, A.; Choi, K.W.; Jain, F.A.; Coman, D.C.; Herman, J.; Perlis, R.; Fava, M.; et al.
Abstract: Introduction: The psychological wellbeing of healthcare workers has been impacted by the high levels of stress many have experienced during the Coronavirus Disease 2019 (COVID-19) pandemic. This study aimed to examine the feasibility and acceptability of a brief online course focused on introducing evidence-based skills that could increase resilience and decreases emotional distress in healthcare workers during the pandemic. Materials and methods: Employees of a large healthcare system completed a mental health survey at baseline, and then one month and two months after some employees participated in an online resilience-enhancement course consisting of three 12–19 min videos focused on mindfulness, mentalization, and self-compassion. Results: A total of 554 participants completed the baseline survey, endorsing moderate to high levels of emotional distress. Of those who completed all three assessments and participated in the course (n = 38), significant improvements in resilience and reductions in emotional distress were found one and two months later, in comparison to those who did not participate in the course (n = 110). Discussion : These findings suggest that a brief, online intervention can improve the mental health of healthcare workers during a crisis such as the COVID-19 pandemic.